Tauhid Landasan Keluarga Dan Masyarakat - Nila Fadilah; Ratna Sari; Muhammad Basyr (CV. Ulil Albab Corp, 2022)
Looking at the state of modern society, which is generally chaotic in monotheistic values, it undermines the order of life of the Islamic community, especially starting with the crisis of faith, moral decadence, and the flow of evil. Therefore, does this study facilitate a discussion of how ideally nurturing monotheistic knowledge is used as the basis of family and community life? This study aims to help us understand the importance of instilling monotheistic knowledge in the lives of all individuals, families and communities. The methodology used in this study is based on literature review approaches such as books, articles, and electronic media. Therefore, this study concludes that the disruption of the living order of modern Islamic society is caused by the knowledge, understanding and practice of monotheistic values. faith. However, when the values of Aqidah are firmly established in all members of the community, an orderly life, a life based on the Koran and Sunnah, is born.